RISK MANAGEMENT IN HEAVY EQUIPMENT PERFORMANCE EVALUATION IN JAKARTA LRT PROJECT PHASE 1B - Faizal Addin Achmad; Bilhan Gamaliel Hartanto (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2026)
Infrastructure projects, especially in the development of mass transportation systems such as light rail transit (LRT), rely heavily on the role of heavy equipment. The use of these machines is a decisive factor in the successful construction of a special mode of rail transport, in which the production capacity of the machine plays a major role in influencing the progress of the project. Therefore, an analysis of the capacity of production volumes is necessary. This study aims to evaluate the production volume capacity of The Jakarta LRT project Phase 1b, including analysis of the capacity of cranes, excavators, dump trucks, compactors, and other heavy equipment. The volumetric method is applied to calculate the volume capacity and productivity of heavy vehicles. The results of the analysis showed that the calculated volume and productivity of the machine have met the target according to the established schedule.